DEVELOPMENT OF MUD CRAB (SCYLLA OLIVACEOUS HERBST) OOCYTE AFTER IN VITRO CULTURE WITH THORACIC GANGLION EXTRACTS OF ESTUARINE CRABS (NEOEPISESARMA LAFONDI JACQUINOT AND LUCAS) - Yushinta Fujaya; Dody Dharmawan Trijuno; Sulistiono; Seiichi Watanabe; Arief Boediono (BIOTROPIA, 2007)
Thorax ganglion was reported as a source of stimulating hormone for gonad development. The aim of this research was to study the development of mud crab (Scylla olivaceous) oocytes cultured in in vitro medium supplemented with thoracic ganglion extracts of Neopisesarma lafondi. Immature crabs with 110 mm carapace width were collected from the mouth of Bawana Marana Rivers, Maros Regency of South Sulawesi, Indonesia. Pieces of ovarian tissues from those crabs were incubated within 24 hours in culture medium (Medium-199 with 100 IU/ml Penicilin-G) supplemented with 2 mg/ml thoracicganglion extract. Result showed that the diameter of mud crab oocytes was increased in congruent with the incubation time. The development was prominent after in vitro incubation for 8 hours (P